Nanomagnet-facilitated pharmaco-compatibility for cancer diagnostics: Underlying risks and the emergence of ultrasmall nanomagnets - Divya S. Parimi; Yamini Gupta; Sreekar Marpu; Chandra S. Bhatt; Tharun K. Bollu; Anil K. Suresh (Elsevier, 2022)
Cancer therapy is a fast-emerging biomedical paradigm that elevates the diagnostic and therapeutic potential of a nanovector for identification, monitoring, targeting, and post-treatment response analysis. Nanovectors of superparamagnetic iron oxide nanoparticles (SPION) are of tremendous significance in cancer therapy because of their inherited high surface area, high reactivity, biocompatibility, superior contrast, and magnetic and photo-inducibility properties. In addition to a brief introduction, we summarize various progressive aspects of nanomagnets pertaining to their production with an emphasis on sustainable biomimetic approaches. Post-synthesis particulate and surface alterations in terms of pharmaco-affinity, liquid accessibility, and biocompatibility to facilitate cancer therapy are highlighted. SPION parameters including particle contrast, core-fusions, surface area, reactivity, photosensitivity, photodynamics, and photothermal properties, which facilitate diverse cancer diagnostics, are discussed. We also elaborate on the concept of magnetism to selectively focus chemotherapeutics on tumors, cell sorting, purification of bioentities, and elimination of toxins. Finally, while addressing the toxicity of nanomaterials, the advent of ultrasmall nanomagnets as a healthier alternative with superior properties and compatible cellular interactions is reviewed. In summary, these discussions spotlight the versatility and integration of multi-tasking nanomagnets and ultrasmall nanomagnets for diverse cancer theragnostics.